2009
DOI: 10.4049/jimmunol.0803510
|View full text |Cite
|
Sign up to set email alerts
|

Anergic T Cells Are Metabolically Anergic

Abstract: Full T cell activation requires TCR engagement (signal 1) in the context of costimulation (signal 2). Costimulation is required for maximal expression of effector cytokines and prevention of T cell anergy. It has become increasingly clear that another major function of costimulation is to up-regulate the metabolic machinery necessary for T cell function. In this report we demonstrate that anergic T cells are metabolically anergic, in that upon full stimulation (signals 1 plus 2) they fail to up-regulate the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
261
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(265 citation statements)
references
References 35 publications
4
261
0
Order By: Relevance
“…For T cell activation, anti-CD28 (37.51), anti-CD3 (2C11), and interleukin 2 (IL-2) were purchased from BD Biosciences or produced as described (23). Antibodies to P-S6 (Ser 240/244 ), S6, P-4EBP-1 (Thr 37/46 ), 4EBP-1, ␤-tubulin, and pan-actin were purchased from Cell Signaling Technologies (Danvers, MA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For T cell activation, anti-CD28 (37.51), anti-CD3 (2C11), and interleukin 2 (IL-2) were purchased from BD Biosciences or produced as described (23). Antibodies to P-S6 (Ser 240/244 ), S6, P-4EBP-1 (Thr 37/46 ), 4EBP-1, ␤-tubulin, and pan-actin were purchased from Cell Signaling Technologies (Danvers, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Sinclair et al (22) showed that the System L transporter, Slc7a5, is a key factor in T cell metabolic reprogramming that directs Leu transport and controls mTORC1 activity (22). Moreover, the Leu antagonist N-acetyl-leucine amide (NALA) inhibits mTORC1 activity and T cell function (23). Similarity, essential amino acid depletion inhibits mTOR and promotes infectious tolerance via generation of regulatory T cells (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During the transition from the naïve resting state to an activated state, T-cell metabolism is substantially increased, including increased uptake of nutrients, accelerated glycolysis, and massive protein and DNA synthesis. In contrast, anergic T cells are thought to be metabolically anergic (6). Because mTOR is a central regulator of metabolism and is regulated by TSC1, we investigated whether TSC1 controls T-cell metabolism.…”
Section: Contribution Of Enhanced Mtorc1 Signaling To the Resistance Ofmentioning
confidence: 99%
“…43 Interestingly, enhanced AMPK activation, which we observed in PP4-deficient T cells, has also been implicated in the induction of anergy. 43,44 The results in this report then lead us to speculate that PP4 may serve as a novel mediator for the anergy avoidance signal, 4,5 so that T cells receiving proper TCR and co-stimulatory signals may proliferate and differentiate normally. In this regard, 2 observations distinguish our CD4cre:PP4 f/f mice from the current paradigm of anergy induction 43 : first, exogenous IL-2 fails to rescue PP4-deficient T cells from their unresponsive state (Fig.…”
Section: Discussionmentioning
confidence: 99%